Ankafiks: Inovasi Media Pembelajaran Digital Berbasis Video Animasi dalam Menulis Karya Fiksi pada Siswa Kelas VIII SMPN 1 Larangan Pamekasan - Ayu Trisnawati; Mochamad Arifin Alatas; Iswah Adriana (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
This research is motivated by the low interest and skills in writing fictional works of grade VIII students of SMPN 1 Larangan Pamekasan due to the use of less interesting and conventional learning media. This study aims to describe the innovation of animated video-based learning media called Ankafiks (Animated Fiction Works) in improving students' ability to write fictional works. The approach used is descriptive qualitative with data collection techniques through observation and interviews. The results of the study showed that the use of Ankafiks media increased students' enthusiasm for learning, made it easier to understand the structure and elements of fictional works, and encouraged students' creativity in writing short stories. This media also received positive responses from teachers and students regarding content, visual appearance, and ease of use. Thus, Ankafiks is worthy of being an alternative innovative digital learning media in improving fiction writing skills in junior high school students.Penelitian ini dilatarbelakangi oleh rendahnya minat dan keterampilan menulis karya fiksi siswa kelas VIII SMPN 1 Larangan Pamekasan akibat penggunaan media pembelajaran yang kurang menarik dan konvensional. Penelitian ini bertujuan untuk mendeskripsikan inovasi media pembelajaran berbasis video animasi bernama Ankafiks (Animasi Karya Fiksi) dalam meningkatkan kemampuan menulis karya fiksi siswa. Pendekatan yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data melalui observasi dan wawancara. Hasil penelitian menunjukkan bahwa penggunaan media Ankafiks meningkatkan antusiasme belajar siswa, mempermudah pemahaman struktur serta unsur karya fiksi, dan mendorong kreativitas siswa dalam menulis cerita pendek. Media ini juga mendapat tanggapan positif dari guru dan siswa terkait isi, tampilan visual, serta kemudahan penggunaan. Dengan demikian, Ankafiks layak dijadikan alternatif media pembelajaran digital yang inovatif dalam meningkatkan keterampilan menulis karya fiksi pada siswa SMP.